Use of Quizizz Learning Media at MAN 1 Banjarmasin - Purnamasari, Reski; Sumiati, Sumiati (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
Quizziz is one of the learning media that creates a learning experience for students. There are features in Quizizz that can be used in learning. This study aims to determine the use of Quizizz  learning media in MAN 1 Banjarmasin students in class X and XI IPS MAN 1 Banjarmasin for the 2022/2023 academic year. The method used in this study is quantitative method. The research population of class X and XI IPS MAN 1 Banjarmasin students amounted to 190 students and the sample amounted to 47 students. Data collection by questionnaire. Analysis of research results with SPSS 25 for Windows.  The results showed that the use of Quizizz learning media in MAN 1 Banjarmasin in grade X and XI IPS in MAN 1 Banjarmasin for the 2022/2023 academic year against 47 students as respondents: Very low (0%), low (2.13%), medium (19.15%), high (31.91%) and very high (46.81%). So based on these results, the use of Quizizz learning media  for MAN 1 Banjarmasin class X and XI IPS for the 2022/2023 school year is at a very high level (46.81%).